Effectiveness of Coffee Husk Compost Application on the Growth of Liberica Coffee Seedlings (Coffea liberica W. Bull ex Hiern.) in Peat Soil - Adiba, Maulana; Maryani, Anis Tatik; Fathia, Nyimas Myna Elsa (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aimed to assess the effect of coffee husk compost on the growth of Liberica coffee seedlings (Tungkal Komposit) in peat soil and identify the optimal dosage for vegetative development. Research Methods: A Completely Randomized Design (CRD) was applied with five treatments and four replications: K0 (100% inorganic fertilizer/control), and K1–K4 (250–400 g compost + 50% inorganic fertilizer). Variables measured included plant height, stem diameter, number of leaves, leaf area, dry shoot weight, dry root weight, and shoot-to-root ratio. Data were analyzed using ANOVA and LSD test at a 5% level. Finding/Results: Compost treatments significantly improved most growth parameters, especially height, stem diameter, leaf area, and biomass. Leaf number showed no significant difference. The best results were achieved with 400 g compost + 50% inorganic fertilizer. Conclusion: Coffee husk compost is effective for enhancing Liberica seedling growth in peat soil. A dosage of 400 g compost with 50% inorganic fertilizer is recommended as optimal.